e-Cidadania como performatividade cidadã - Ribeiro, Eloá Augusta (2023)
Citizenship is a constantly evolving concept that permeates various approaches, meanings, and understandings. Its semantic evolution coincides with the very history of society. Scientific and technological development has established the foundations of society through systematized knowledge, step-based methods, specific metrics and processes, in the construction of a contemporary society that is hyperconnected, fragmented, and technological. In this context, this dissertation aims to investigate the new disposition of relationships that has been established in the exercise of citizenship through hyperconnection and technological mediation, which characterize contemporary society. Through a phenomenological approach, we identify ecitizenship as a phenomenon that emerges as a cultural form of exercising citizenship in the networked technological society, presenting itself as the main vector for citizenry construction in contemporaneity, due to its performative nature.